The impact of ICT use on livelihoods of microenterprises : case of South Africa - Makoza, Frank (Department of Information Systems, 2015)
This thesis aims to contribute to the understanding of impact of using Information and Communications Technology (ICT) on the livelihoods of microenterprises in the developing countries context.